Welfare transformations and expectations of sameness. Living on the margins in Denmark. - Camilla Merrild; Rikke Sand Andersen (Nordic Journal of Social Research)
In Denmark, as in other welfare societies worldwide, the organisation and ideology of welfare are becoming increasingly influenced by neoliberal ideas. In practice, this means that the original intention behind the provision of social support, which was grounded in the notion of social responsibility, is gradually being pushed aside by notions of responsibilisation, with concepts such as deservingness and work ethic appearing to dominate the discourse. Based on long-term fieldwork and interviews conducted with socially disadvantaged Danes living on social security, this article engages with the current debates regarding responsibility and highlights some of the challenges arising from living a life that diverges from what has been termed Danish ‘in-between middle-classness’. We argue that the divergence between the promise of welfare, the current landscape of political regulation and expectations of individual responsibility leads to new forms of uncertainty, as experienced by those who depend on the services provided by the welfare state. One implication of this is that welfare seems to increasingly be tied to an agenda of sameness, whereby citizenship stems less from a imagination of sameness than from an expectation of sameness.